2019
DOI: 10.1017/s1751731119000247
|View full text |Cite
|
Sign up to set email alerts
|

Predicting feed intake and feed efficiency in lactating dairy cows using digesta marker techniques

Abstract: Direct measurement of individual animal dry matter intake (DMI) remains a fundamental challenge to assessing dairy feed efficiency (FE). Digesta marker, is currently the most used indirect technique for estimating DMI in production animals. In this meta-analysis we evaluated the performance of marker-based estimates against direct or observed measurements and developed equations for the prediction of FE (g energy-corrected milk (ECM)/kg DMI). Data were taken from 29 change-over studies consisting of 416 cow-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
2
8
0
1
Order By: Relevance
“…The estimated value in the present study is consistent with the acrosslactation repeatability estimate of 0.66 documented in 5,162 lactating dairy cows (Berry et al, 2014). In a recent study, Guinguina et al (2019) also reported a repeatability estimate of 0.65 for DMI in lactating dairy cows in digestion studies. We estimated a repeatability Correlations were controlled for feeding level, experiment, diet within experiment, and period within experiment effects.…”
Section: Between-cow Variation and Repeatabilitysupporting
confidence: 91%
“…The estimated value in the present study is consistent with the acrosslactation repeatability estimate of 0.66 documented in 5,162 lactating dairy cows (Berry et al, 2014). In a recent study, Guinguina et al (2019) also reported a repeatability estimate of 0.65 for DMI in lactating dairy cows in digestion studies. We estimated a repeatability Correlations were controlled for feeding level, experiment, diet within experiment, and period within experiment effects.…”
Section: Between-cow Variation and Repeatabilitysupporting
confidence: 91%
“…Moreover, both fecal output and herbage intake were estimated by double marker technique using Cr 2 O 3 and iNDF as markers, respectively, which are also reported to have bias associated to herbage and fecal sampling protocol and marker recovery in feces (Guinguina, Ahvenjärvi, Prestløkken, Lund, & Huhtanen, 2019;Velásquez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A model including BFY, MY and LW achieved the best accuracy of prediction, compared to one with only one of these traits. These traits have also been found to be associated with GFE and, therefore, good predictor traits for GFE in several other studies (Linn et an exceptionally strong prediction power (R 2 = 0.98), which was much higher than for one developed previously from multiparous Holstein data (R 2 = 0.76) (Guinguina et al 2019). Beard (2018) developed models with much lower prediction ability (R 2 = 0.45) using primiparous Canadian Holstein data, and including milk yield, milk components and live weight only.…”
Section: Gross Feed E Ciencymentioning
confidence: 51%
“…There was a low antagonistic relationship (-0.23) between LW and GFE, which was however not signi cant. This negative association is a well-documented phenomenon, and is attributable to the fact that larger cows demand more nutrients for body maintenance, resulting in less feed being available for milk production (Linn et al, 2009;Vallimont et al, 2011;Ben Meir et al, 2018;Guinguina et al, 2019). Thus, LW could contribute towards the prediction of GFE.…”
Section: Lahart Et Al 2019)mentioning
confidence: 99%
See 1 more Smart Citation